2010
DOI: 10.1111/j.1600-0838.2009.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of socioeconomic status on the physical activity in adolescents: a systematic review of the evidence

Abstract: The relationship between physical activity and socioeconomic status (SES) is evident in the adult population, but is much discussed with regard to adolescents. The main objective of this review was, therefore, to clarify whether there is a relationship between physical activity and SES in adolescents. Computerized searches were conducted in the databases PubMed, ISI Web of knowledge and SPORT-Discus to identify all relevant articles up to July 2009. Other review articles, descriptive or theoretical articles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
310
7
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(359 citation statements)
references
References 65 publications
21
310
7
21
Order By: Relevance
“…Increased educational level of mothers was associated with increased MVPA in their daughters. Jekauc et al found that socioeconomic status can affect the RPA recommendations only in girls, and girls with low socioeconomic status were more likely to obey the RPA recommendation than girls with high socioeconomic status were (41) that is in contrast to prior reviews (42,43). It has been indicated Health Scope.…”
contrasting
confidence: 42%
“…Increased educational level of mothers was associated with increased MVPA in their daughters. Jekauc et al found that socioeconomic status can affect the RPA recommendations only in girls, and girls with low socioeconomic status were more likely to obey the RPA recommendation than girls with high socioeconomic status were (41) that is in contrast to prior reviews (42,43). It has been indicated Health Scope.…”
contrasting
confidence: 42%
“…It is also worth mentioning that children's independent mobility is a factor significantly associated with their time spent playing outdoors, considering it depends on several variables including the parent's perception on the neighborhood's safety 27 . Because of inferior supervised time, low levels of outdoor play in HPE children can be due to the mothers' concerns on the neighborhood's safety and on the safety of the living areas 34 . Thus, it seems important to have further study on what children can and cannot do when they are outdoors, and to identify the quality of the opportunities for outdoor play 35 .…”
Section: Discussionmentioning
confidence: 99%
“…To obtain more equity in health, it is important to address health-related behaviours (the Swedish Commission for Equity in Health, 2017). Adolescents’ socioeconomic status (SES) and their ethnicity have been identified as contributing factors for unhealthy eating (Mattisson, 2016) and physical activity (Stalsberg & Pedersen, 2010). These health habits have the potential to decrease the risk of illness and can thus contribute to reducing the health gap between adolescents from different SES groups (Mattisson, 2016; World Health Organization, 2016).…”
Section: Introductionmentioning
confidence: 99%